In the Space of Cumulative Trauma: Lessons from a Hungarian Trauma-Novel in Vojvodina - Faragó, Kornélia (Porównania, 2023)
In the case of deep trauma, literature is often unable to speak. In the Hungarian literature of Vojvodina, the general silence concerning the changes of empire and the reprisals describes the traumatic experience as an impulse that is impossible to put into a narrative. Nándor Burány’s book-length trauma novel, Összeroppanás (Implosion), published in 1968, looked back on the events from a quarter of a century later and for the first time thematised the task of processing transgenerational trauma. The novel’s distinctive feature is that it introduces the concept of trauma itself by asking questions about the identification of the time of the traumatic rupture. The real subject of his poetics is the way trauma works and its ineffable nature. The double vision so characteristic of trauma stories becomes here an important structural figure. In the moody world of trauma-induced thinking, the necessity and impossibility of speech at once torments the central figure of the novel. The novel is set in a space of cumulative trauma and processes trauma as a social construction based on lived experience. It also makes the point that trauma in this space cannot be located in a single inherent violent past event, but rather in a series of dates and events.